An Analysis of Approbation and Sympathy Maxims Based on Leech’s Politeness Principles in Emma Movie - Rini Nuraini; Sudarsono; Suhartono , Luwandi; Bunau , Eusabinus; Susilawati , Endang (Journal of Scientific Research, Education, and Technology (JSRET), 2024)
This research aims to identify the most dominant type of politeness principles especially on approbation and sympathy maxims and the application both of them in Emma movie. This research was descriptive study. The corpus of this research was the transcript of dialogue spoken by the characters in Emma movie. The data are collected using the theory of Creswell which consists of five interrelated steps. These steps respectively deal with identifying the movie, gaining information relate to that movie, considering the focus of information, designing tool named datasheet, and administering the data. Then the data were analyzed descriptively using the theory from Miles, Huberman, & Saldana which consists of data condensation, data display, and drawing conclusion. The researcher used the theory of Leech to analyze the most dominant type of politeness principles especially approbation and sympathy maxims and also the application of both of them in the movie. The findings of this research found the most dominant type of politeness principles in Emma movie is approbation maxim with 37 data (72.55%) out of 51 data. It is followed by sympathy maxim with 14 data (27.45%) out of 51 data. The application of these two maxims happens in family discourse. This is because the context of language usage in the early 19th-century English society. The abuse of power and wealth, all prove that the class status of Emma’s family plays a significant role in the shaping how the politeness works in society.